The standard of living among the poor across Europe. Does employment make a difference? - Wolf, Fridolin; Lohmann, Henning; Böhnke, Petra (European societies, 2022)
Employment does not always guarantee sufficient income and a decent standard of living anymore. In this paper, we analyze the relationship between income poverty and material deprivation for employed and unemployed individuals across Europe. To do so, we focus on relevant mechanisms at the individual and institutional levels. We examine how economic, structural and institutional factors shape the relationship between employment, poverty and deprivation. We explore our subject using EU-SILC data from 2015 and cross-national macro-level data from the OECD, Eurostat and UNECE. According to our findings, employment is associated with a higher standard of living even among the poor and when controlling for savings and income level, which may point to the non-monetary benefits of employment. At the macro level, we show that the impact of employment on the living standard of the poor varies according to economic conditions and institutional settings. Our results suggest that policies that promote integration into the labour market without taking into account the quality of jobs and working conditions devalue gainful employment in terms of maintaining a decent standard of living.